2011
DOI: 10.3386/w17248
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Analysis of a Wage Subsidy for Cape Town Youth

Abstract: Recognizing that a credible estimate of a wage subsidy's impact requires a model of the labor market that itself generates high unemployment in equilibrium, we estimate a structural search model that incorporates both observed heterogeneity and measurement error in wages. Using the model to examine the impact of a wage subsidy, we find that a R1000/month wage subsidy paid to employers leads to an increase of R660 in mean accepted wages and a decrease of 15 percentage points in the share of youth experiencing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…If youth who are nonparticipants are considered searching in the model, then the estimates might overstate learning about employability because a period of nonparticipation would be treated as a failed job search. However, a companion paper using CAPS (Levinsohn and Pugatch, 2014) finds that 64 per cent of those who permanently exit school and never report searching nonetheless find employment by the end of the sample, suggesting that labor market participation is not synonymous with active search for these youth. Any resulting bias should therefore not be very large.…”
Section: The Cape Area Panel Studymentioning
confidence: 98%
“…If youth who are nonparticipants are considered searching in the model, then the estimates might overstate learning about employability because a period of nonparticipation would be treated as a failed job search. However, a companion paper using CAPS (Levinsohn and Pugatch, 2014) finds that 64 per cent of those who permanently exit school and never report searching nonetheless find employment by the end of the sample, suggesting that labor market participation is not synonymous with active search for these youth. Any resulting bias should therefore not be very large.…”
Section: The Cape Area Panel Studymentioning
confidence: 98%
“…Several studies conducted after the ETI was proposed in 2010 were of the opinion that it had the potential to change the employment prospects for youth (Burns et al 2010;Levinsohn and Pugatch 2014;Mtembu and Govender 2015;National Treasury 2011). Burns et al (2010) argued that the wage subsidy might be successful in creating jobs in South Africa if it was associated with skills training, especially in industries that are sensitive to labour costs, and should have a focus on youth.…”
Section: The Employment Tax Incentive Policymentioning
confidence: 99%
“…Burns et al (2010) argued that the wage subsidy might be successful in creating jobs in South Africa if it was associated with skills training, especially in industries that are sensitive to labour costs, and should have a focus on youth. Levinsohn and Pugatch (2014) suggested that the wage subsidy could decrease the share of youth experiencing long-term unemployment. conducted a randomized control trial before the policy was enacted to examine how a wage subsidy might affect youth unemployment in the South African context.…”
Section: The Employment Tax Incentive Policymentioning
confidence: 99%